PENGARUH PENGEMBANGAN KARIR DAN JOB INSECURITY TERHADAP TURNOVER INTENTION: Studi Pada PT. BPR Nusamba Mengwi - Ni Luh Eva Riantini; I Wayan Suartina; I Gede Aryana Mahayasa (Journal of Applied Management Studies, 2021)
Companies with high turnover intention show that there are many problems that have resulted in employees choosing to move to another company. This study aims to determine the effect of career development and job insecurity on turnover intention at PT. BPR Nusamba Mengwi partially and simultaneously. This research was conducted at PT. BPR Nusamba Mengwi. The number of respondents taken was 77 employees with a saturated sampling method. The data analysis technique used multiple linear regression analysis. Based on the analysis, it was found that career development and job insecurity had a positive and significant effect on turnover intention at PT. BPR Nusamba Mengwi partially and simultaneously. Based on the research results, it can be suggested that PT. BPR Nusamba Mengwi evaluates policies related to employees by looking at career development factors, job insecurity, and turnover intention to companies.